Oxygen uptake by rat jejunum in media devoid of Na+ (Revista Española de Fisiología, 1971)
It has been studied the effect of the substitution of Na+ in the medium on the oxygen uptake of jejunal strips of rat.In incubation experiments of three hours, the substitution of Na+ diminished the oxygen uptake increasing in the following order: choline, Tris, Li+, sucrose or man nitol. The greatest inhibition occured with the non ionic substitutes and with Li+ among the ionic ones.After a pre-incubation of one hour in Na+ free media, the tissue respiration in a medium with Na+ remained strongly inhibited when the substitute used was mannitol or Li+. In the other cases the recovery was more or less complete.These effects are attributed to changes in the intracellular ionic composition induced according to the nature of the substitute for Na+ in the exterior medium. In the case of Li+ and mannitol, are also suggested changes in the structure or enzymatic systems of the cell.The diminished oxygen uptake in media devoid of Na+ can not be explained solely by the suppression of the Na+ pump. There are other factors more directly involved in the biochemical respiratory processes that can be altered in a partially or non-reversiblc manner.These factors that affect the availability of cellular energy must be taken into con sideration when studying the relationship between the active transport of diverse sub stances and the ionic ambient.